Gut microbiota and traumatic brain injury: insights from an antibiotic-free cohort - Wu, Hao; Huo, Yuqi; Fang, Wei; Guo, Jinlin; Wang, Xiaoqin; Su, Li; Cheng, Gang (Frontiers in Microbiology, 2026)
IntroductionTraumatic brain injury (TBI) is a major global health concern, leading to persistent neurological deficits and systemic complications. While animal studies have shown the association between TBI and the gut microbiota, human evidence, particularly in the early post-injury period, remains scarce.MethodsIn this study, we profiled the gut microbiota of TBI patients within 8 days of hospitalization using 16S rRNA sequencing, integrating clinical metadata and excluding individuals who had received antibiotics within the preceding month.ResultsAlthough alpha diversity remained similar between groups, beta diversity was significantly altered in TBI patients relative to healthy controls, accompanied by increased inter-individual variability. Differential abundance analysis revealed a depletion of short-chain fatty acid (SCFA)-producing taxa, e.g., Eubacterium, Agathobacter, and Faecalibacillus intestinalis, alongside an enrichment of dysbiosis-associated genera, including Escherichia and Shigella. Notably, Lactobacillus, a γ-aminobutyric acid-producing genus, was elevated in TBI patients, potentially reflecting a compensatory response to neural injury. Functional prediction suggested reduced SCFA biosynthetic capacity in TBI patients, whereas biofilm formation and several other fitness-related processes were enriched. Integrating gut microbiota with clinical and demographic variables, a machine learning model moderately predicted Glasgow Coma Scale scores, with age, inflammatory markers, and differentially abundant bacterial taxa as major contributors.DiscussionCollectively, these findings indicate that TBI is associated with dysbiosis of the gut microbial and altered metabolic potential.